VOLUNTARY CHILDLESS SEBAGAI PILIHAN TAHDID AL-NASL UNTUK MEWUJUDKAN KELUARGA BERENCANA DALAM PERSPEKTIF HILAH - Pertiwi, Endah Mustika; Helim, Abdul (Borneo : Journal of Islamic Studies, 2024)
The background of this study is the childfree phenomenon that has re-emerged in the public eye amidst the decline in the ideal age marriage rate and the still high rate of early marriage. This study describes the phenomenon of voluntary childlessness, or the absence of children as an option in the context of tahdid al-Nasl (birth control) to realize family planning, with a hilah perspective approach. The focus of the study is the application of hilah in the case of voluntary childless couples who assume that they have supported the family planning program with their willingness to live without children so that they are able to reduce the birth rate. This study is normative with a literature study approach to collect primary legal materials. The results of this study indicate that voluntary childlessness is included in the hilah ghair syar'iyyah, or cases that are not permitted; the practice of family planning is permitted in Islam, but there are terms and conditions for its implementation and the goals to be achieved.